Improving Parameters of Controller for T-Type Inverter in Open-Circuit Fault of Power Switch Condition - Do, Đức Trí; Truong, Ngọc Anh (Journal of Technical Education Science, 2022)
In this paper, a three-level quasi-switched boost T-type inverter that operates in normal and power switch failure power switch conditions (3L qSBT2I-UFM) is presented. This structure is formed by two symmetrical impedance networks and a three-level T-type inverter. Besides the advantages of multilevel voltage source inverters (VSIs), the structure of the 3L qSBT2I-UFM is characterized by its switching capabilities. When the open-circuit failure occurs in power switch, the reduction in output power will be compensated by the boost characteristic of the quasi-switched boost. In addition, improving the control coefficient will help the system respond quickly to ensure output power quality. The ability to operate under power switch fault conditions is demonstrated by experimental results under normal and fault conditions. To verify the properties of this multi-level quasi-switched boost, an experimental model was also built to verify the experimental results.